Numerical methods for linear control systems : design and analysis - Datta, Biswa Nath (Elsevier Academic Press, 2004)
Numerical Methods for Linear Control Systems Design and Analysis is an interdisciplinary textbook aimed at systematic descriptions and implementations of numerically-viable algorithms based on well-established, efficient and stable modern numerical linear techniques for mathematical problems arising in the design and analysis of linear control systems both for the first- and second-order models. MATLAB-based software is included for implementing all of the major algorithms from the book. * Unique coverage of modern mathematical concepts such as parallel computations, second-order systems, and large-scale solutions * Background material in linear algebra, numerical linear algebra, and control theory included in text * Step-by-step explanations of the algorithms and examples * Includes MATLAB-based solution software.